Phāprūam sētthakit kānkhā kap prathēt ph̄ưanbān Thai-S̜̄oP̜̄oP̜̄o. Lāo Čhangwat N̜̄ong Khāi (Samnakngān Phānit Čhangwat N̨̄ong Khāi, 1997)
Trade and economic relationship of Nong Khai Province with neighboring countries in Northeastern Thailand.